The use of Location Based Instagram Data for Tourism Potential Analysis in Kabupaten Gunung Kidul - Muhammad Irham Akbar Hasri; Purnama Budi Santosa (Universitas Gadjah Mada, 2018)
Gunungkidul Regency is one of five regencies in Yogyakarta Province which is rich of natural tourism destination objects. Each tourism object has its own potential and characteristic that distinguishes one with other tourism objects. However, the tourism potency have not been exposed to public properly, and the local government has not sufficiently use the data of visitors as the basis for planning and development of tourism objects in Gunungkidul Regency. This research tries to evaluate the use of BIG DATA, especially social media data, to analyze the tourism potency based on the public opinions and visits. For this purpose, Instagram data was utilized as the main data for the analysis. The data was collected between December 18, 2017 to February 3, 2018 using Instagram API. The data then was pre-processed to clear or filter the duplication data, to filter the data based on selective location or study area namely Gunungkidul Regency, as well as to filter the data which match with the topic of the research namely “tourism”. Some analysis then were conducted, namely spatial analysis, statistical analysis, and caption analysis. The spatial and statistical analysis were aimed to find spatial pattern of tourists visits at several locations in the form of spatial density of each tourism destinations with respect to temporal aspect. Analysis of captions is done by filtering Instagram data by using some keywords that can indicate tourism potency. Data was visualized using Carto Builder. Results show that some effort is needed to utilize the Instagram data for this purpose. The data is efficient and effective to be used to visualize spatial-temporal pattern of visitors at tourism destinations, as well as to understand tourism destinations objects potency in Gunungkidul Regency. However, this analysis cannot be done in realtime due to a limitation in collecting data from Instagram API.